The morale of disabled players and its relationship with some variables - Barrak, Natiq (Journal of Physical Education, 2024)
This research aimed at detecting to morale level of disabled players as well as knowing the differences in degree of morale and influence of experience, educational achievement and age on it. The researcher used the descriptive method according the case study method in addition to the morale scale prepared by the researcher after ensuring validity, reliability, and objectivity of this scale. The subjects were (25) players from Anbar Governorate teams who participated in tournaments for 2022-2023 season. The researcher concluded that level morale of the players was low, in addition that there was no effect of educational attainment, experience, and age on the level of morale. Finally, the researcher stressed the necessity to pay attention the humanitarian, social, as well as technical and administrative aspects of clubs and federations in addition to spreading familiarity, love and affection among players and encouraging team play.